Preparation and evaluation of chitosan-tripolyphosphate nanoparticles suspension as an antibacterial agent - Hakim Bangun, Steven Tandiono, Anayanti Arianto (Journal of Applied Pharmaceutical Science, 2018)
Objectives: The purpose of this study was to prepare and evaluate the chitosan-tripolyphosphate (CS-TPP) nanoparticles suspension as an antibacterial agent. Material and Methods: CS-TPP nanoparticles suspension was prepared by the ionic gelation method with various concentrations of CS and TPP. The prepared nanoparticles suspension was evaluated for particle size, sedimentation, the interaction between CS and TPP, particles morphology, and antibacterial activity against Staphylococcus aureus (Gram positive) and Pseudomonas aeruginosa (Gram negative). Results: The results showed that among all of the concentrations used, the formulation of 0.25% CS and 0.1% sodium TPP resulted in the smallest particles size (average diameter was 238.17 nm) with spherical morphology, no sedimentation after centrifugation at 6,000 rpm for 2 hours, and gave the highest antibacterial activity against Staphylococcus aureus and P. aeruginosa. Conclusion: CS-TPP nanoparticles can be formed by using CS and TPP solution at a certain concentration and the CS-TPP nanoparticles suspension has an antibacterial activity.
Keywords: Chitosan, sodiumtripolyphosphate, nanoparticles, antibacterial activity.